Increasing the competitiveness of Romanian farms in the post-accession period - Viorica Gavrilă (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The present study investigates various issues related to farm competitiveness, using viability indicators, such as Net Value Added and Net Income of farms, as well as indicators regarding factor productivity, highlighting the relationship between productivity, farm typology and farm size. EUROSTAT and European Commission statistics based on FADN survey from the period 2007-2018 were used. The results reveal that the evolution of income indicators mainly depended on the increase of the physical farm size and on labour force diminution. Both farm specialization and the physical and economic farm size are correlated with labour productivity. Improving the efficiency of production factors should contribute to reducing the disparities in the development level of the agricultural sector.
Keywords: Q12; J24; 330; farms; productivity; competitiveness